2022
DOI: 10.3390/land11020274
|View full text |Cite
|
Sign up to set email alerts
|

On-Site Analyses as a Decision Support Tool for Dredging and Sustainable Sediment Management

Abstract: Beneficial use of dredged sediments, either in harbours or waterways, is based on their potential as alternative resources. Such sediments can be considered as bulk materials for industrial needs, which is predicated on their current waste status or meeting end-of-waste constraints. They also can be an integral part of beneficial use projects using sediments as a bulk component, including civil engineering and landscaping. This is particularly important for beneficial use projects focusing on climate change ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…For instance, Gang et al [34] have shown that high water contents with exceeded concentrations of HHMs, and a large fraction of fine particles in dredged materials could be successfully improved by mixing with S/S agents. Other authors [5,21,[35][36][37][38] have proposed assessment strategies and environmental tools for managing MSs. Pasciucco [17] and Barjoveanu [39] implemented a life cycle assessment (LCA) of the environmental impacts during the application of S/S to remediate MSs.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Gang et al [34] have shown that high water contents with exceeded concentrations of HHMs, and a large fraction of fine particles in dredged materials could be successfully improved by mixing with S/S agents. Other authors [5,21,[35][36][37][38] have proposed assessment strategies and environmental tools for managing MSs. Pasciucco [17] and Barjoveanu [39] implemented a life cycle assessment (LCA) of the environmental impacts during the application of S/S to remediate MSs.…”
Section: Discussionmentioning
confidence: 99%
“…Baseline characterization of a potential site is an important management tool for sediment reuse [22]. In advance of sediment emplacement, a comprehensive geochemical survey of the site was undertaken, supplemented by previous ground investigation reports.…”
Section: Methodsmentioning
confidence: 99%
“…On-site instruments provide immediate results and allow dynamic or adaptive sampling strategies, as well as allowing operational decisions in real time. Lemière et al (2022) provides an extensive overview of analytical techniques on-site and in the lab that were used for the pilot sites in the GedSet and SURICATES projects. In this paper, the focus is on the Portable X-ray fluorescence (pXRF) for solids and on the multiparametric probe for water.…”
Section: Descriptionmentioning
confidence: 99%
“…The results of the on-site pXRF and multiprobe measurements for the three pilot locations, supplemented with alternative insite and near real time analyses, are published by Lemière et al (2022). As an example, the main potential source of metal contamination for the regeneration area at Bowling (Fig.…”
Section: Use Of On-site Analyses By Pxrf As a Decision Support Toolmentioning
confidence: 99%